Preparation and properties of poly(lactic acid)/lignin‐modified polyvinyl acetate composites. Issue 7 (26th August 2020) - Shu, You; Luo, Qionglin; Wang, Mingliang; Ouyang, Yuejun; Lin, Hongwei; Sheng, Liping; Su, Shengpei
Abstract: Poly(lactic acid)(PLA) has good application in the field of packaging because of its good biodegradability, tensile strength, and film‐forming properties. However, the disadvantages of high brittleness and high cost limit the wider application of PLA. PLA/lignin‐modified polyvinyl acetate (L‐PVAc) composites with excellent toughness were prepared by melt blending PLA with modifier L‐PVAc. The mechanical properties, thermal properties and morphology of the composites were characterized to evaluate the effect of L‐PVAc content on the properties of the composites. The results showed that the introduction of L‐PVAc could increase the impact strength, elongation at break, glass transition temperature, melting temperature and the degree of crystallinity of PLA/L‐PVAc composites. When the L‐PVAc content reached up to 20.0 wt%, the impact strength, elongation at break, glass transition temperature, melting temperature and the degree of crystallinity of the composites were increased by 298.2%, 167.5%, 3.8%, 1.8%, and 78.8%, respectively compared to pure PLA due to the good toughness of PVAc and heterogeneous nucleation of lignin. This research can promote the high‐value utilization of lignin and the application of PLA in the fields of clothing, agriculture, medical and hygiene. Abstract :